PERANCANGAN POWER SUPPLY UNTUK CHARGING STATION KENDARAAN LISTRIK RODA DUA DENGAN SISTEM PLTS ON GRID - Nadhif Dewayana, Zevardy; Setiawan, I Nyoman; Dwi Giriantari, Ida Ayu (Program Studi Teknik Elektro UNUD, 2024)
Electric vehicles use electrical energy as a substitute for fossil energy. Like gasoline vehicles that require gasoline filling facilities, electric vehicles also require electric energy charging facilities or commonly referred to as charging stations. One of the utilizations of solar power plant can be used for charging electrical energy at the charging station. In this study, a Power Supply Design was carried out for Charging Station for Two-Wheeled Electric Vehicles with Solar Power Plant System on grid in Widya Sabha Building Parking Lot, Udayana University. With the calculation of the energy needed in the Power Supply, the solar power plant design and manufacturing costs can be made. The design of this charging station can accommodate 10 electric motorbikes with solar power plant that can provide energy for 2 electric motorbikes per day for 9 hours of work alternately. By using 11.450 Wp solar panels arranged in series and 1 inverter with a capacity of 4.6 kW, this design produces 8.229 MWh per year. The total initial investment in this design based on market prices in Indonesia is IDR 99.213.000. Based on the investment feasibility, it shows that the investment in this design is feasible to implement.